2017
DOI: 10.1007/s12350-016-0664-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional compared to anatomical imaging in the initial evaluation of patients with suspected coronary artery disease: An international, multi-center, randomized controlled trial (IAEA-SPECT/CTA study)

Abstract: Objective To test the hypothesis that, in the initial evaluation of patients with suspected coronary artery disease (CAD), stress myocardial perfusion imaging (MPI) would result in less downstream testing than coronary computed tomographic angiography (CCTA).MethodsIn this international, randomized trial, mildly symptomatic patients with an intermediate likelihood of having CAD, and asymptomatic patients at intermediate risk of cardiac events, underwent either initial stress-rest MPI or CCTA. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Among the total included studies, 7 RCTs investigated the impact of CCTA strategy in patients with acute chest pain: the Coronary Computed Tomographic Angiography for Systematic Triage of Acute Chest Pain Patients to Treatment (CT‐STAT) trial, the CT Coronary Angiography Compared to Exercise ECG (CT‐COMPARE) trial, the CATCH trial, the Prospective Randomized Outcome Trial Comparing Radionuclide Stress Myocardial Perfusion Imaging and ECG‐gated CCTA (PROSPECT), the Prospective First Evaluation in Chest Pain (PERFECT) trial, the study by Faisal Nabi et al, and the ACRIN‐PA 4005 trial . Five RCTs enrolled patients with stable chest pain: the Cardiac CT for the Assessment of Pain and Plaque (CAPP) trial, the Computed Tomography vs Exercise Testing in Suspected Coronary Artery Disease (CRESCENT) trial, the PROMISE trial, the SCOT‐HEART trial, and the International Atomic Energy Agency (IAEA)‐SPECT/CTA study . The mean or median follow‐up durations of the included studies varied significantly, ranging from 6 months to 42 months.…”
Section: Resultsmentioning
confidence: 99%
“…Among the total included studies, 7 RCTs investigated the impact of CCTA strategy in patients with acute chest pain: the Coronary Computed Tomographic Angiography for Systematic Triage of Acute Chest Pain Patients to Treatment (CT‐STAT) trial, the CT Coronary Angiography Compared to Exercise ECG (CT‐COMPARE) trial, the CATCH trial, the Prospective Randomized Outcome Trial Comparing Radionuclide Stress Myocardial Perfusion Imaging and ECG‐gated CCTA (PROSPECT), the Prospective First Evaluation in Chest Pain (PERFECT) trial, the study by Faisal Nabi et al, and the ACRIN‐PA 4005 trial . Five RCTs enrolled patients with stable chest pain: the Cardiac CT for the Assessment of Pain and Plaque (CAPP) trial, the Computed Tomography vs Exercise Testing in Suspected Coronary Artery Disease (CRESCENT) trial, the PROMISE trial, the SCOT‐HEART trial, and the International Atomic Energy Agency (IAEA)‐SPECT/CTA study . The mean or median follow‐up durations of the included studies varied significantly, ranging from 6 months to 42 months.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings contrast with observations that CCTA-based strategy may result in a significant reduction in MI in stable chest pain patients 22 25 26. Use of stress electrocardiography as a comparator arm in some studies performed in outpatient settings may exaggerate the benefits of CCTA-based strategy due to relatively inferior performance of stress electrocardiography in ischaemia detection compared with stress imaging 27. Alternatively, detection of anatomic coronary artery disease (regardless of individual lesion severity) may prompt adjustment of medical regimen such as aggressive lipid-lowering therapy and lifestyle modification that decrease the long-term risk of acute coronary events 28.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Karthikeyan et al, this was indeed a factor in the IAEA-SPECT/CTA study's failure to meet the target enrollment: only six of the planned 13 sites were approved to enroll participants. 4 Studies with stricter inclusion/exclusion criteria were also found to be more likely to be terminated for insufficient recruitment. 5 A primary concern for termination due to slow accrual is the potential loss of study power.…”
Section: See Related Article Pp 507-517mentioning
confidence: 99%
“…Note that the planned sample size for the IAEA-SPECT/CTA study was 500 subjects, which, assuming a 10% rate of loss to follow-up, would have led to 90% power to detect a significant difference in the primary endpoint, the rate of downstream testing. 4 Even though only 303 patients (60.6% of the target enrollment) were recruited, the study still had 83% power.…”
Section: See Related Article Pp 507-517mentioning
confidence: 99%